PENGARUH PUPUK ORGANIK SAMPAH KOTA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SEMANGKA (Citrullus vulgaris Schard) - Jeinarti Piyohu; Nurmi ,; Suyono Dude (Jurnal Lahan Pertanian Tropis (JLPT), 2022)
Research aimed to investigating the influence of waste organic fertilizer of Gorontalo City towards Growth and Crop of with watermelon (Citrullus vulgaris Schard). This research was done in village of Tanah Putih, Sub-districh of Botupingge, Bone Bolango Regency That start from May to July 2016. This research applies completely randomized design which consist of 4 levels municipal waste organic fertilizer which are P0 without fertilizer, P1 of 10 t ha-1, P2 of 20 t ha-1, P3 of 30 t ha-1. Every treatment was repeated 3 times, thus there are 12 plots of research. Research finding reveals that treatment of waste organic fertilizer of the City has significant influence towards Grouth and Crop of watermelon that is heigh of plant on age of 2 Weeks after Planting and 3 WAP, amount of flowers to be fruit. Waste Organic fertilizer of the City with dose of 30 t ha-1 geves the best influence towards Grouth and crop of Watermelon.Keywords: Municipal, Waste, Growth, Yield, Watermelon